Intervention strategies in early childhood to prevent celiac disease—a mini-review - Andrén Aronsson, Carin; Agardh, Daniel (Frontiers in Immunology, 2023)
Higher intake of gluten during in childhood is associated with increased risk of celiac disease. The incidence of celiac disease peaks shortly after the time-point when associations with higher gluten intake during the second and third year of life occur. Additional environmental factors are most likely necessary for celiac disease to develop. It is hypothesized that gastrointestinal infections increase gut permeability and exposures to gluten. Alternatively, infections may lead to gut dysbiosis and chronic inflammation with leakage of self-antigens that mimic gluten peptides that leads to an autoimmune-like response. Different gluten interventions to prevent celiac disease have been proposed. Early clinical studies suggested an optimal time-point introducing gluten between 4-6 months of age while the infant is being breastfed. However, later clinical trials on reduced gluten intake given to infants have shown no protection of celiac disease if gluten introduction was delayed or if gluten was introduced in small amounts during the child’s first year of life. Still, more randomized clinical trials (RCTs) are warranted to answer the question if a reduced amount of gluten, not only at time of introduction during infancy, but also in a longer timeframe, will prevent children at genetic risk from lifelong celiac disease. It needs to be clarified whether dietary interventions are effective strategies to be proposed as future prevention of celiac disease in the general population. The present minireview provides an overview of ongoing or completed RCTs which have focused on interventions during early childhood with the aim to prevent celiac disease.